Differences in ankle stabilizing function between the upper and lower fiber bundles of the anterior talofibular ligament: an anatomical study - Mutsuaki Edama; Yuto Sekii; Kodai Sakamoto; Tomonobu Ishigaki; Hirotake Yokota; Ryo Hirabayashi; Makoto Komiya; Chie Sekine; Tomoya Takabayashi; Noboru Sato (Scientific Reports)
Abstract This study aimed to clarify the differences in the stabilizing functions of the upper and lower fiber bundles of the anterior talofibular ligament (ATFL). Five Thiel-fixed cadavers (10 ft) were divided into an upper fiber bundle cut group (upper-cut group, 5 ft) and a lower fiber bundle cut group (lower-cut group, 5 ft). The angular conditions were set as 0-degree ankle dorsiflexion, 15-degree plantar flexion, and 30-degree plantar flexion. Anterior drawer and inversion stresses were applied using a Telos stress device at 120 N. Measurements were obtained when the upper and lower fiber bundles of the ATFL were intact (intact condition) and when either the upper or lower fiber bundle was severed (cut condition). For each group, the distance between the lateral malleolus and talus was measured using an ultrasound diagnostic device under both the intact and cut conditions and compared. Regarding anterior drawer stress, the displacement rate (%) significantly increased in both the upper- and lower-cut groups under the cut condition at 30-degree plantar flexion. Meanwhile, for the inversion stress, only the upper-cut group demonstrated a significantly increased displacement rate (%) under the cut condition at 0-degree dorsiflexion. No significant difference in either anterior drawer stress or inversion stress at any angle was observed between the two groups. Both the upper and lower fiber bundles of the ATFL may be involved in stabilizing ankle function during anterior drawer stress at 30-degree plantar flexion. In addition, the lower fiber bundle may play a role in stabilizing the ankle during inversion stress at 0-degree dorsiflexion.